Variations in sympathovagal balance, psychogalvanic reflex and isometric grip force in females with polycystic ovarian syndrome- an exploratory study - Kothari, Ruchi; Jogad, Yugal; Gheewala, Shabbir; Bokariya, Pradeep; Shivkumar Verma, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Poly-cystic ovarian syndrome (PCOS) is an endocrine ailment and recently emerging cause of infertility amongst reproductive females. The disease is associated with multifactorial etiologies. Autonomic dysfunction is cause or result of this disorder is yet a paradox. Various autonomic function tests can be done to reveal this dilemma. Heart rate variability is pivotal amongst these and assesses trivial variations between two heart beats and stands as a marker of cardiac risk. Sympathetic skin response checks integrity of sympathetic reflex tract. Isometric grip force relates contracting force and electromyography with a person’s heart rate during exercise. As there is meagre published evidence on autonomic function testing in central Indian women with PCOS, this study was undertaken on the PCOS patients and their data was compared with regularly menstruating healthy controls. Methods: A cross sectional study was performed on 35 healthy controls and 35 PCOS diagnosed patients of age range 18 to 42 years short-term HRV was recorded using ECG and RR interval using power lab system. Thereafter SSR was obtained using bio amplifier by giving standard acoustic stimuli. The patients were then asked to perform isometric grip force exercise using grip force transducer to obtain various related parameters. Results: The mean age group of controls was 22.62±2.15 years and that of among cases was 23.29±4.26 years. Compared to healthy controls PCOS patients had higher waist circumference, lower HF Norm whereas higher VLF norm and LF/HF ratio, delayed SSR latency while hand grip strength was significantly higher in the control group as compared to the PCOS patients. LF/HF ratio, mean HR, waist circumference and SSR latency were positively correlated to each other and negatively correlated to mean hand grip strength. Conclusions: PCOS females have altered adrenergic status as compared to normal women. Various autonomic function tests like HRV, SSR and hand grip strength exercise can be useful in evaluating these patients as the disease exposes them to various co morbid risk factors.